Pengaruh ketimpangan pendapatan, pengeluaran perkapita, angka harapan hidup dan upah minimum terhadap kedalaman kemiskinan di Provinsi Jambi - Sandi Arianugrah; Yulmardi; Parmadi (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the influence of Income Inequality, Per Capita Expenditure, Life Expectancy, and Minimum Wage on Poverty Depth in Jambi Province using time series data and a multiple linear regression method processed through EViews 12. The research was conducted to understand the key factors that shape the dynamics of poverty depth in the region, thereby providing a basis for formulating more targeted policy interventions. The results indicate that among the four variables examined, only Life Expectancy has a significant effect in reducing poverty depth. This finding suggests that improvements in public health quality and increases in life expectancy contribute meaningfully to enhancing the welfare of the population. Meanwhile, Income Inequality, Per Capita Expenditure, and Minimum Wage do not show significant effects, indicating that these variables have not yet provided strong direct impacts on changes in poverty depth. Overall, this study emphasizes the importance of strengthening the health sector as a priority strategy for poverty alleviation efforts in Jambi Province.